2018
DOI: 10.1089/tmj.2017.0134
|View full text |Cite
|
Sign up to set email alerts
|

Acceptance of Telemonitoring Among Patients with Obstructive Sleep Apnea Syndrome: How is the Perceived Interest by and for Patients?

Abstract: It seems reductive to consider telemonitoring as a simple tool of surveillance to support adherence. It may be preferable to consider telemonitoring as a follow-up proposal. This will allow for more reactive management and close to the needs of the patients, in particular as telemonitoring is, in general, well accepted by patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 24 publications
2
13
0
3
Order By: Relevance
“…Another concern is related to patients' perceptions of telemonitoring. In a recent study from TURINO et al [50], patients were not worried about being remotely observed through telemonitoring systems, but in another study of patient acceptance of telemonitoring, despite the fact that the majority (78%) of the 160 studied patients expressed a favourable attitude toward telemonitoring, 40% consider this device intrusive [64].…”
Section: Discussionmentioning
confidence: 91%
“…Another concern is related to patients' perceptions of telemonitoring. In a recent study from TURINO et al [50], patients were not worried about being remotely observed through telemonitoring systems, but in another study of patient acceptance of telemonitoring, despite the fact that the majority (78%) of the 160 studied patients expressed a favourable attitude toward telemonitoring, 40% consider this device intrusive [64].…”
Section: Discussionmentioning
confidence: 91%
“…To that end, telemedicine interventions must be enlightened by more research on their usability by both patients and healthcare professionals [26]. Even though telemedicine is in general well accepted by OSA patients [27], recent work by TURINO et al [10] showed telemonitoring of CPAP signals alone did not improve CPAP treatment compliance and was associated with lower patient satisfaction. Moreover, from the professionals' side there are well-known factors preventing the widespread implementation of this strategy, including poor organisation in healthcare institutions, regulations and clinical practice guidelines, and staff training.…”
Section: Discussionmentioning
confidence: 99%
“…This finding was explained by the lack of in-person contact in the intervention arm, whereas clinical appointments were only scheduled for the control arm. 80 Also, in the study of Bros and colleagues, 151 a majority (78%) of patients expressed a favorable attitude toward telemonitoring, but nearly 40% considered the telemonitoring device like intrusive. Telemonitoring also encompasses the risk to mask some aspects of care, by relying excessively on technical parameters, forgetting the clinical context.…”
Section: Patient Satisfactionmentioning
confidence: 98%